10. Potency of Clove Leaf Ethanol Extract (Syzygium aromaticum L) Against Differentiation of Leukocytes in White Rats (Rattus norvegicus) Experiencing Incision Wounds - Charles Eko Masihin; M Kaihena; A J A Unitly (Universitas Syiah Kuala, 2021)
This study aims to determine the difference in leukocytes of white rats (Rattus norvegicus) that suffered from incision wounds after being treated with clove leaf ethanol extract (Syzygium aromaticum L). The study used 15 white rats divided into five groups, and each was replicated three times. P1 is a negative control group, namely, rats with incisions made without medication. P2 is a positive control; namely, rats made incisions and were given betadine. P3 is a group of rats with incisions made and given clove leaf ethanol extract at a dose of 0.09 g/head/day for 14 days. P4 is a group of rats with incisions made and given clove leaf ethanol extract at a dose of 0.18 g/head/day for 14 days. P5 is a group of rats with incisions made and given clove leaf ethanol extract at a dose of 0.36 g/head/day for 14 days. After 14 days, the rats were dissected, and their blood was taken for analysis using a hematology analyzer to determine the difference in leukocytes. The results showed that there was a significant difference when presenting the ethanol extract of clove leaves (P0.05). It was concluded that presenting the ethanolic extract of clove leaf increased the differentiation of rats with incisional wounds.